(untitled) (Fiep Bulletin - online, 2011)
Physical training is used to produce physiological changes and adaptations that make the muscles more powerful and accurate to perform certain movements. The muscle fibers that comprise a muscle are classified according to criteria physiological, biochemical and metabolic fibr5as in slow-twitch and oxidative (SO), fast twitch and glycolytic metabolism and oxidative (FOG) and fast twitch fibers and metabolism exclusively glycolytic (FG). These fibers react differently depending on the stimulus that is applied to them. Aiming to describe the effect of exercise compared aerobic and anaerobic exercise on the fiber used 30 Wistar rats with 90 days of age divided into groups Sedentary (S), aerobic training (Tae) Trained and Anaerobic (Tan). Aerobic exercise consisted of 1 hour of swimming with a load of 5% of body weight three times a week for 8 weeks. The anaerobic training consisted of four sets of suspension of 3 minutes with 1 minute intervals between the series on a cable attached to two iron rods. After the training period picked up the biceps brachii and pectoralis major were placed in liquid nitrogen, cut in a cryostat and stained with hematoxylin and eosin, histochemical reaction for NADH-TR and myofibrillar ATPase reaction was pre-incubated at pH 4.3, 4.6 and 9.4 for the identification of its fibers. After identifying their cross-sectional areas were measured. The SO and FOG fibers did not differ in the extent of their areas when subjected to two years, since the FG fibers were increased in both the aerobic training, anaerobic training in how to. We conclude that the FG fiber hypertrophy and give more power to muscle contraction.